Work schedule flexibility and parking preferences - Wei-Shiuen Ng (Journal of Transport and Land Use)
The flexibility of work schedule affects the number of commute trips made per week and the number of hours spent at work, which can influence congestion and transportation emission levels. Understanding the linkages between the flexibility of work schedule and travel behavior will provide insights for policies targeted at transportation and parking demand management. This study uses the University of California (UC) Berkeley campus as a study site. UC Berkeley is one of the largest employers in the San Francisco Bay Area with over 11,000 employees, leading to a wide range of employment type, job characteristics, and varying levels of work schedule flexibility. A total of 86 one-on-one interviews were conducted with UC Berkeley employees. This study explores common factors that contribute to UC Berkeley employees’ parking preferences and considers how academic discipline or employment type could affect work schedule, which in turn influences travel behavior. Driving is the most popular choice across employment type and job categories. However, not all employees who drive alone have the same parking location preferences. The flexibility of work schedule is one of the key factors that influences parking preferences at the workplace, especially when there are alternative parking locations.